KEWENANGAN DAN KEKUASAAN PERADILAN AGAMA - Amin, M. Misbahul; Sholichah, Binty Alifatus (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
The competence or authority of religious courts is formulated as the state's power to receive, examine, adjudicate and decide, as well as resolve certain cases between people of the Islamic faith to uphold law and justice. Islamic courts include courts that handle all types of cases according to universal Islamic teachings. Therefore, wherever the principle of justice is applied, the principle of equality is applied. because there is only one Islamic law and comes from the same source of law, namely the Al-Quran and the Sunnah. Meanwhile, religious court is Islamic court in Indonesia, meaning that religious court is the term for Islamic court in Indonesia. This is because the types of cases handled are related to the Islamic religion, so that overall they are types of cases according to the Islamic religion.